TERAPI INTERPERSONAL DAN MOTIVATIONAL INTERVIEWING PADA GANGGUAN AFEKTIF BIPOLAR DAN GANGGUAN PENGGUNAAN ZAT - Christantio Brilian Richard Legoh (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Psychoactive substance misuse is a global health problem that affects biological, psychological, and social aspects of individuals. Substance addiction, including the use of multiple substances such as alcohol, nicotine, and methamphetamine, is associated with mental disorders, impaired social functioning, and an increased risk of relapse and medical complications. This paper aims to examine the concept of polysubstance addiction, its underlying neurobiological mechanisms, and biopsychosocial management approaches. The method employed is a literature review of psychiatry textbooks and recent scientific articles related to substance addiction and psychotherapeutic interventions, with a publication range from 2021 to 2026 obtained from databases such as PubMed, ScienceDirect, and Google Scholar, and using inclusion criteria focusing on studies addressing addiction mechanisms, psychological comorbidities, and evidence-based therapeutic interventions. The findings indicate that addiction is a chronic condition involving alterations in the brain reward system, increased impulsivity and compulsivity, and is influenced by genetic, psychological, and sociocultural factors. Management requires a multimodal approach combining pharmacological treatment for comorbid symptoms (such as depression and psychosis) and non-pharmacological therapies, including Cognitive Behavioral Therapy, Interpersonal Psychotherapy, and Motivational Interviewing. The integration of psychosocial interventions has been shown to improve patient engagement, reduce relapse rates, and enhance quality of life. In conclusion, the management of polysubstance addiction should be conducted holistically and continuously to support long-term recovery. ABSTRAK Penyalahgunaan zat psikoaktif merupakan masalah kesehatan global yang berdampak pada aspek biologis, psikologis, dan sosial individu. Adiksi zat, termasuk penggunaan multipel seperti alkohol, nikotin, dan metamfetamin, berkaitan dengan gangguan mental, penurunan fungsi sosial, serta meningkatnya risiko kekambuhan dan komplikasi medis. Tulisan ini bertujuan mengkaji konsep adiksi zat multipel, mekanisme neurobiologis, serta pendekatan penatalaksanaan berbasis biopsikososial. Metode yang digunakan adalah tinjauan pustaka terhadap buku teks psikiatri dan artikel ilmiah terkini terkait adiksi zat dan intervensi psikoterapi, dengan rentang publikasi tahun 2021–2026 yang diperoleh dari basis data PubMed, ScienceDirect, dan Google Scholar, serta menggunakan kriteria inklusi berupa artikel yang membahas mekanisme adiksi, komorbiditas psikologis, dan intervensi terapi berbasis bukti. Hasil kajian menunjukkan bahwa adiksi merupakan kondisi kronis yang melibatkan perubahan sistem reward otak, peningkatan impulsivitas dan kompulsivitas, serta dipengaruhi faktor genetik, psikologis, dan sosiokultural. Penatalaksanaan memerlukan pendekatan multimodal melalui terapi farmakologis untuk gejala komorbid (depresi dan psikosis) serta terapi nonfarmakologis seperti Cognitive Behavioral Therapy, Interpersonal Psychotherapy, dan Motivational Interviewing. Integrasi intervensi psikososial terbukti meningkatkan keterlibatan pasien, menurunkan kekambuhan, dan memperbaiki kualitas hidup. Simpulan kajian ini menegaskan bahwa penanganan adiksi zat multipel perlu dilakukan secara holistik dan berkesinambungan guna mendukung pemulihan jangka panjang.